Alternate livelihood development for â€˜Ailaâ€™ affected tribal people through aquaculture in Bali Island of the Sunderban, West Bengal, India - Chakrabarti, P. P.; Ghosh, A.; Mohapatra, B. C.; Barik, N. K.; Das, A.; Kumar, K.; Mondal, S. C.; Majhi, D.; Mistry, A.; Jayasankar, P. (Indian Journal of Fisheries, 2018)
Bali Island is one of the mangrove reclaimed zone of Sunderban, West Bengal, inhabited mostly by tribal communities. Lack of employment opportunities and limited access to market as well as urban areas are characteristic features of livelihood of the people. The devastating cyclone â€œAilaâ€ which hit the island during 2009, resulted in ingress of saline water, degradation of land and water resources, loss of biodiversity, destruction of animal and farm infrastructure which further led to a major loss to the livelihood system. Aimed at restoring livelihood of these tribal people, aquaculture based interventions were initiated by the ICAR-Central Institute of Freshwater Aquaculture (ICAR-CIFA), Bhubaneswar, during the period 2013-14 among 51 tribal families in Bali Island. The interventions were effected by creation of alternative livelihood options through composite fish culture (single component), duck-cum-fish culture (multi-component) and hatchery production of fish seed (single component). Scientific management of the aquaculture ponds helped to achieve an average fish production of 4 - 6 t ha-1 yr-1 from a benchmark of around 1 t ha-1 yr-1. One lakh fingerlings of Labeo rohita and Labeo bata were also produced through FRP carp hatchery. In addition, fish-duck farming trials also created nutritional security through egg, duck meat and fish production. The economic impact assessment revealed that investment of `11.05 lakhs by ICAR-CIFA, resulted in a net incremental wealth generation of `20.67 lakhs. For a typical tribal family of average 5 members, 67% alternative livelihood support was achieved through duck-cum-fish farming.